Effects Of Intellectual Capital On Organizational Performance: The Mediating Role Of Performance Measurement System - Danish, Rizwan Qaiser; Cheema, Amna Umer; Shekh, Labiba; Ali, Hafiz Fawad; Saeed, Sania; Hasnain, Muhammad (The journal of contemporary issues in business and government, 2021)
Purpose: The primary goal of this study is to empirically analyze the influence of innovative culture and trust on intellectual capital and examine the impact of intellectual capital on organizational performance through the mediation effect of the performance measurement system in the aviation sector of Pakistan. Methodology: The target population of the study comprises ground-level and aircraft staff from the aviation sector of Pakistan. The convenience sampling technique is used to collect the data. The pre-structured questionnaire is used to gather data is an indication that this is a quantitative study. SEM is used to measure the hypothesized model. Findings: Using SEM in AMOS v22, the outcomes of the study show that organizations can efficiently improve their non-financial performance by measuring the main drivers of IC (i.e., trust and innovative culture).